Emerging functions of tissue-resident eosinophils - Gurtner, Alessandra; Crepaz, Daniel; Arnold, Isabelle C. (The Journal of experimental medicine, 2023)
Eosinophils are typically considered tissue-damaging effector cells in type 2 immune-related diseases. However, they are also increasingly recognized as important modulators of various homeostatic processes, suggesting they retain the ability to adapt their function to different tissue contexts. In this review, we discuss recent progress in our understanding of eosinophil activities within tissues, with particular emphasis on the gastrointestinal tract, where a large population of these cells resides under non-inflammatory conditions. We further examine evidence of their transcriptional and functional heterogeneity and highlight environmental signals emerging as key regulators of their activities, beyond classical type 2 cytokines.